Understanding the Performance Impacts Of Cross-Platform Development On IoT Applications - Santos, Fabio C. dos; Marques-Neto, Humberto Torres Marques; Mini, Raquel Aparecida de Freitas (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
The Internet of Things (IoT) is an increasingly evident reality in everyday life. IoT makes possible to interconnect physical objects through a heterogeneous computer network, creating new ways to manage infrastructures. In the IoT systems, smartphones have a fundamental role due to their computational capacity and resources. Nowadays, the major mobile devices have several types of sensors that can be used to monitor and collect data from the physical world, such as GPS, accelerometer, barometer, among others. Thus, IoT developers have used different cross-platform frameworks to improve their productivity and to make the software maintainability easily and fast. In this context, the goal of this work is to understand the performance impacts of some cross-platform frameworks for IoT application development. To do this, we built three versions of the same Android application of an IoT system using (1) Ionic, (2) React Native, and (3) Java, which uses some smartphone's sensors commonly used in IoT applications, such as GPS, WiFi, and BLE. For each resource and performance evaluation metric for each version of our application, we created a specific test-case to measure and to compare the analyzed cross-platform framework. Our results showed slight differences between the three versions of our IoT application in some analyzed metrics.